Influence of rice husk ash particles on microstructure and tensile behavior of AA6061 aluminum matrix composites produced using friction stir processing. (March 2017) - Dinaharan, Isaac; Kalaiselvan, Kumaravel; Murugan, Nadarajan
Abstract: Rice husk ash (RHA) is an economical and potential reinforcement for producing aluminum matrix composites (AMCs). The present work reports the production and characterization of AA6061/18 vol% RHA AMC using the novel method friction stir processing (FSP). The microstructure was studied using optical microscopy (OM), scanning electron microscopy (SEM) and electron back scattered diagram (EBSD). A homogenous dispersion of RHA particles was obtained in the composite. No agglomeration or segregation was observed. The produced composite exhibited a fine and equiaxed grain structure. RHA particles fragmented during FSP. An improvement in the tensile strength was observed subsequent to reinforcement of RHA particles. The fracture surface was dispersed with fractured RHA particles confirming excellent interfacial bonding with the aluminum matrix. Graphical abstract: Highlights: Utilization of waste rice husk ash to synthesis aluminum matrix composites. Friction stir processing was used to produce AA6061/RHA composite. Homogenous dispersion of RHA particles were achieved. RHA particles encountered fragmentation during processing. Incorporation of RHA particles enhanced the tensile strength.